[As3M(As3Pb3)]3− (M = Nb, Ta): Ternary Heterometallic Clusters with Early Transition Metal Atoms and Aromatic [Pb3]2−. Issue 7 (3rd June 2021) - Shu, Cong‐Cong; Qiao, Lei; Muñoz‐Castro, Alvaro; Sun, Zhong‐Ming
Main observation and conclusion: Two ternary clusters, [As3 Nb(As3 Pb3 )] 3− 1 and [As3 Ta(As3 Pb3 )] 3− 2, were directly extracted from "K8 NbPbAs5 " and "K8 TaPbAs5 " intermetallic solid in the presence of ethylenediamine and 2.2.2‐crypt, respectively. Both 1 and 2, comprising an electron‐poor early transition metal‐atom Nb or Ta coordinated to a As3 triangle and a bowl‐like As3 Pb3, were characterized by single crystal X‐ray diffraction, energy dispersive X‐ray (EDX) and electrospray ionization mass‐spectrometry (ESI‐MS). They also represent the first examples of the Pb‐As hybrid in solution‐based Zintl anion chemistry and DFT calculations revealed a σ‐aromaticity of the [Pb3 ] 2− unit. Abstract : Ternary clusters [As3 MAs3 Pb3 ] 3− (M = Nb, Ta), directly extracted from quaternary intermetallic solid K8 MPbAs5, are made up of electron‐deficient transition atoms, an As3 triangle and a hypho As3 Pb3 unit. The σ‐aromaticity of the [Pb3 ] 2− unit was demonstrated by DFT calculations.